Building an endobariatric program: lessons learned - Badurdeen, Dilhana; Hedjoudje, Abdellah; Itani, Mohamad; Fayad, Lea; Farha, Jad; Dunlap, Margo; Cheskin, Lawrence; Schweitzer, Michael; Koller, Kristen; Hartman, Christian; Oberbach, Andreas; Kashab, Mouen A.; Kalloo, Anthony; Kumbhari, Vivek (Endoscopy International Open, 2020)
The emphasis on treating obesity has never been more critical, yet the complexity of delivering care has become more intricate due to new procedures, variable insurance coverage, and inconsistent reimbursement. This is our experience building an endobariatric program and treating overweight and obese patients with endobariatric therapies (EBTs) over 3 years. The primary intention of this manuscript was to educate the reader on how to build an endobariatric program, identify barriers, and provide succinct solutions to establish a successful program. The secondary aim was weight loss outcomes of procedures offered at our institution. We compiled a list of lessons learned, based on the difficulties we experienced to make it easy for others embarking on this journey. Herein, we present a business development strategy to overcome impediments, whilst offering high quality service. The high cost and lack of insurance coverage are significant barriers. Marketing can be costly and is often a factor that is ignored particularly early on, when finances are limited. However, it is an integral component of growing the program. The percentage total body weight loss (%TBWL) at 6 and 12 months post ESG was 17.8 ± 6.48 and 20.6 ± 8.3 (P < 0.001), respectively. The %TBWL at 6 months post IGB was 14.9 ± 9.8 for the Orbera IGB and 12.6 ± 7.4 for the Reshape IGB. There was a trend of preference for ESG compared to IGB placement over the 3 years. The key to building a successful endobariatric program is a motivated physician leader, collaborative bariatric surgeons, institutional support, and marketing. Insurance coverage will likely occur in the near future and programs must be prepared to manage the massive influx of patients that will likely request these procedures.